Development of Combinatorial Optimization Models with Discrete Mathematics Methods in Mathematical Physics Courses - Astalini, Astalini; Pino-Fan, Luis Roberto; Boonsiri, Somjai; Zainudeen, U.L.; Aye, Tin Nwe; Duong, Vu (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to develop a combinatorial optimization model based on discrete mathematical methods that can be applied to mathematical physics problems in complex systems, such as molecular energy configurations and viscoelastic system simulations. Methodology: The study used a development approach with ADDIE design (Analysis, Design, Development, Implementation, Evaluation). Data were obtained through interviews, simulations, and instrument validation involving lecturers and students of mathematical physics. Main Findings: The results of the study showed that the developed model had an average accuracy of 85% and a time efficiency of 2.5 seconds per iteration. This model also received positive feedback from users, with an average satisfaction score of 4.6 out of 5. Novelty/Originality of this study: The novelty of the research lies in the integration of discrete mathematical methods with combinatorial optimization to solve complex mathematical physics problems.